PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Irvansyah, Rio; Wijayanti, Wiwik (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study analyzes the role of the school principal's leadership at SD Muhammadiyah Jogokariyan in enhancing education quality. Employing a qualitative-phenomenological approach, this study explores how a transformational leadership style focusing on systemic innovation and a long-term vision serves as a key factor in the school's success.  The principal fulfills seven key roles educator, manager, administrator, supervisor, leader, innovator, and motivator with an integrated and systemic approach.  The implemented strategies include management digitalization, a collaborative quality assurance system, and structural innovations such as the "dual homeroom teacher" policy. Findings reveal a strong correlation between transformational leadership and a significant increase in academic achievement (ANBK) and school accreditation.  This report concludes that leadership based on role modeling and proactive system design is an effective model for building sustainable educational quality.